CONCEPT ANALYSIS OF RESILIENCE UNIVERSITY STUDENT - soeli, yuniar mansye; Daulima, Novy Helena Catharina; Mustikasari, Mustikasari; Martha, Evi (Universitas Aisyah Pringsewu, 2025)
ABSTRACTUniversity student resilience is a crucial factor in academic success and psychological well-being. This study aims to explicate the concept of developing resilience among university students. Walker and Avant's concept analysis approach will be employed to analyze and clarify the understanding of resilience development. This concept analysis will help identify key attributes that support resilience development, such as coping skills, social support, optimism, and self-belief. The Walker and Avant framework will be used to construct a comprehensive framework for developing student resilience, encompassing intervention programs, assessment, and evaluation. The results of this concept analysis are expected to contribute to the development of effective programs to enhance student resilience, enabling them to better cope with academic and non-academic challenges